Increased levels of anti-BSA antibodies in children with Down syndrome - Grace, Sian L.; Mortimer, Georgina L.; Kozhakhmetova, Aizhan; Leveret, Jamie; Newton, Richard; Reimand, Koit; Shield, Julian P. H.; Uibo, Raivo; Williams, Alistair J. K.; Gillespie, Kathleen M. (Frontiers in Endocrinology, 2023)
Autoimmune diabetes occurs more often in the first 2 years of life in children with Down’s Syndrome (DS) compared with the general population. We previously observed increased frequencies of islet autoantibodies, including insulin autoantibodies (IAA), in children with DS. Assays for IAA using 125I-labelled insulin require competition to overcome cross reactivity with antibodies to the cow’s milk protein, bovine serum albumin (BSA). 125I-IAA assay results suggested that levels of antibodies to BSA may also be increased in children with DS. The aim of this study therefore was to determine whether the levels of anti-BSA antibodies differed in children with DS compared with controls. Samples were available from two populations with DS: one from the UK, (UK DS cohort n=106, 58 male, median age 12.5 years) and one from Estonia (Estonian DS cohort: n=121, 65 male, median age 9.75 years). A UK control population was provided by sex and age-matched healthy siblings of probands participating in the Bart’s Oxford (BOX) family study of type 1 diabetes. A competitive-displacement radiobinding assay (RBA) and a Dissociation Enhanced Lanthanide Fluoroimmunoassay (DELFIA) were developed to measure and confirm anti-BSA antibody levels. HLA class II genotype was analysed by PCR using sequence specific primers (PCR-SSP). Overall, levels of anti-BSA antibodies were increased in those with DS compared with controls (p<0.0001) but this was not HLA associated. Increased levels of anti-BSA antibodies may reflect an immune defect in maturation or increased gut permeability in children with DS.